Association studies on the bovine lipoprotein lipase gene polymorphism with growth and carcass quality traits in Qinchuan cattle. Issue 2 (April 2016) - Gui, Linsheng; Jia, Cuiling; Zhang, Yaran; Zhao, Chunping; Zan, Linsen
Abstract: Lipoprotein lipase (LPL) is considered as an essential enzyme in lipid deposition and tissue metabolism. It has been proposed to be a lead candidate gene for genetic markers of lipid deposition and energy balance. In this paper, polymorphisms in the LPL gene were investigated in 554 Chinese Qinchuan cattle by PCR-RFLP and DNA sequencing. Seven single nucleotide polymorphisms (SNPs) were identified, which included one mutation (g.91C > T) in the 5′untranslated region (UTR), four synonymous mutations (g.17015A > G, g.18362G > A, g.18377T > C and g.19873T > C) and two mutations (g.25225A > G and g.25316T > G) in the 3′UTR. The frequencies of SNP g.18377T > C and g.25316T > G were skewed from Hardy–Weinberg equilibrium in all the samples (chi-square test, P < 0.05). An association analysis showed that five loci (except for g.91C > T and g.18377T > C) were significantly correlated with some growth and carcass quality traits. These results demonstrate that LPL might be a potential candidate gene for marker-assisted selection (MAS). Highlights: We identified seven SNPs of bovine LPL gene. We analyzed the genotype distribution and genetic diversity of all detected SNPs. Effects of single markers on six economical traits were analyzed in Qinchuan cattle.